2020
DOI: 10.1186/s40792-020-01004-7
|View full text |Cite
|
Sign up to set email alerts
|

Post-esophageal atresia repair double acquired tracheoesophageal fistulas treated successfully by gastric transposition: a case report

Abstract: Background Postoperative recurrence of tracheoesophageal fistula (TEF) is a frequent complication in the repair of esophageal atresia (EA). Based on the recent etiologic classification, a TEF that develops in a different new pathway from the original one is categorized as an acquired TEF. The TEFs that fall into this category have been reported to be refractory and their mechanisms have not been fully understood. Here, we report the complicated case of an acquired TEF derived from mediastinitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…No apparent cause of RTEF was observed when reviewing the operation video and perioperative management. Although anastomotic leakage has been reported to be the main cause of RTEF ( 5 , 8 , 9 ), in this case, esophago-esophageal anastomosis was considered to have caused no apparent problem by postoperative course. A previous study has reported that RTEF can occur from inflammation due to leakage in the trachea when a TEF is single-ligated using a 4-0 absorbable braided suture ( 3 ).…”
Section: Discussionmentioning
confidence: 80%
“…No apparent cause of RTEF was observed when reviewing the operation video and perioperative management. Although anastomotic leakage has been reported to be the main cause of RTEF ( 5 , 8 , 9 ), in this case, esophago-esophageal anastomosis was considered to have caused no apparent problem by postoperative course. A previous study has reported that RTEF can occur from inflammation due to leakage in the trachea when a TEF is single-ligated using a 4-0 absorbable braided suture ( 3 ).…”
Section: Discussionmentioning
confidence: 80%